2012
DOI: 10.1071/as11078
|View full text |Cite
|
Sign up to set email alerts
|

Transformations from WISE to 2MASS, SDSS and BVI Photometric Systems: II. Transformation Equations for Red-Clump Stars

Abstract: Abstract:We present colour transformations for the conversion of Wide-Field Survey Explorer W1, W2, and W3 magnitudes to the Johnson-Cousins BVI c , Sloan Digital Sky Survey gri, and Two Micron All Sky Survey JHK s photometric systems, for red clump (RC) stars. RC stars were selected from the Third Radial Velocity Experiment Data Release. The apparent magnitudes were collected by matching the coordinates of this sample with different photometric catalogues. The final sample (355 RC stars) was used to obtain me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…3 Identification of the RC stars in WISE Bilir et al (2012) showed that the RC stars can be effectively detectable in W 1, W 2 and W 3 bands of the WISE photometry while dwarfs can be found using W 1 and W 2 (Bilir et al, 2011). We preferred W 1 and W 3 bands in order to identify the RC stars in WISE.…”
Section: The Datamentioning
confidence: 99%
See 1 more Smart Citation
“…3 Identification of the RC stars in WISE Bilir et al (2012) showed that the RC stars can be effectively detectable in W 1, W 2 and W 3 bands of the WISE photometry while dwarfs can be found using W 1 and W 2 (Bilir et al, 2011). We preferred W 1 and W 3 bands in order to identify the RC stars in WISE.…”
Section: The Datamentioning
confidence: 99%
“…We tested the adopted absolute magnitudes and colours of the RC stars es-Table 3 Modes of distributions for the absolute magnitudes and a colour in WISE for the RC stars with σ π /π ≤ 0.15 (see Table 1). The evaluated values from the transformation equations (TEs; Bilir et al, 2012) are also given. Differences between two sets of the data are in the last column.…”
Section: Mode (Mag)mentioning
confidence: 99%
“…A mean value for the M K s absolute magnitude with weak metallicity dependence can be used for distance estimation which is rather useful for the Galactic structure and interstellar extinction. Examples can be found in López-Corredoira et al (2002, Cabrera-Lavers, Garzón, & Hammersley (2005);Cabrera-Lavers et al (2007a, 2007b, 2008 and Bilir et al (2012) and references therein.…”
Section: Scale-length Of the Thin Discmentioning
confidence: 99%
“…Yaz et al (2010) obtained transformation between optical and NIR bands for red giants. Bilir et al (2012) extended this study to mid-infrared bands by using Radial Velocity Experiment (RAVE) Third Data Release (DR3) data (Siebert et al 2011). Both works provide absolute magnitudes for a given photometry from another one.…”
Section: Introductionmentioning
confidence: 99%